Se-doped nickel-cobalt sulfide nanotube arrays with 3D networks for high-performance hybrid supercapacitor. Issue 20 (15th October 2022) - Zhou, Ao; Chi, Ruitong; Liu, Rong; Shi, Yingjie; Zhang, Zhixiao; Che, Hongwei; Wang, Guangsuo; Mu, Jingbo; Wang, Yanming; Zhang, Xiaorong
Abstract: In this study, Se doped nickel-cobalt sulfide (Se–NiCoS) nanotube arrays with three-dimensional (3D) networks are prepared on nickel foam via a facile hydrothermal method combined with selenide reaction. The 3D networks are formed by interconnected nanosheets grown on the surface of nanotubes. Results show that the dopant amount of Se in nickel-cobalt sulfide (NiCoS) has obvious effects on both the structure and performance of the Se–NiCoS. The combined contribution of Se dopant and the unique 3D network structure can greatly improve the electrochemical performance of NiCoS. Compared with the pristine NiCoS nanotube array, the Se–NiCoS nanotube arrays demonstrate enhanced areal capacitance (2.00 and 1.48 F cm −2  at 1 and 20 mA cm −2, respectively) and cyclic stability (capacitance retention rate of 91.2% after 5000 cycles at 5 mA cm −2 ). Furthermore, the hybrid supercapacitor assembled with Se–NiCoS nanotube arrays and carbon nanotubes (CNTs) as positive electrode and negative electrode can deliver an energy density of 37.7 Wh kg −1 at a power density of 798.4 W kg −1 . This study indicates that the 3D network structured Se–NiCoS nanotube arrays have a good practical application value in supercapacitor devices.